2007
DOI: 10.1016/j.jfe.2006.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Variation of federal cost-share programs in the United States and the inducement effects on tree planting

Abstract: A long existing question associated with federal cost-share programs in the United States has been whether these public subsidies have induced or substituted for landowners' private investment in tree planting. This study reexamined the relationship between public funding and private investment behavior in the past 50 years by employing a state space model with time-varying parameters. Three regions, i.e., the South, North, and West were formed and compared. The analysis revealed that the relationship has chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…The southern states accounted for 90% of the program's allocation. Annual appropriations for FIP have ranged from $10 to $15 million in the last decade (Sun, 2007).…”
Section: Major Regeneration Programs and The Response Of Landownersmentioning
confidence: 99%
See 1 more Smart Citation
“…The southern states accounted for 90% of the program's allocation. Annual appropriations for FIP have ranged from $10 to $15 million in the last decade (Sun, 2007).…”
Section: Major Regeneration Programs and The Response Of Landownersmentioning
confidence: 99%
“…These studies also examined the economic efficiency of these programs, practice retention rate, capital substitution, equity, and subsidiary effects (Gaddis et al, 1995). Previous studies generally agreed that these programs have successfully influenced the management of NIPF lands and stimulated more planting activities (Boyd, 1984;Nagubadi et al, 1996;Mehmood and Zhang, 2001;Sun, 2007). However, in spite of the benefits, these studies also revealed that NIPF landowners have not always utilized these programs.…”
Section: Introductionmentioning
confidence: 99%
“…One could speculate that since private forest owners are not the primary audience of these programmes and the money available to them is rather small, they are not interested in performing the subsidized activities. Forest affinity for forest subsidies has been explored before in many contexts such as cost-sharing programmes (Song et al, 2014;Sun et al, 2009;Sun, 2007) and particularly in relation to wood mobilisation, where owners' attitudes to incentives and advise have been widely explored (Lawrence, 2018). Numerous studies have shown that private forest owners in Europe are mostly multi-objective owners, recreationists, indifferent owners or conservationists and not-for-profit managers (see Ficko et al, 2017 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…They found that cost-share programs consistently ranked among the most effective policy tools for encouraging loggers, landowners, and foresters to apply best management practices. Despite the documented effectiveness of cost-share programs, concerns have been raised that landowners who participated in cost-share programs would have undertaken the supported practice anyway, although the financial assistance often enabled the landowners to treat additional acres beyond what would otherwise have occurred (De Steiguer, 1984;Hardie and Parks, 1991;Kilgore et al, 2007;Sun, 2007).…”
Section: Introductionmentioning
confidence: 99%